Analysis of air temperature trends: City of Podgorica (Montenegro) - Bačević Nikola; Valjarević Aleksandar; Kićović Dušan; Milentijević Nikola; Ivanović Marko; Mujević Meliha (The University Thought: Publication in Natural Sciences, 2020)
This paper presents the results of the analyzed trends for three categories of parameters: average annual air temperature (YT), average maximum air temperature (YTx) and average minimum air temperature (YTn) for the Podgorica Meteorological Station in the Republic of Montenegro. The aim of this paper is to present possible climate changes based on the results obtained from the analyzed air temperature trends. The methodology is based on the application of: a) linear trend equations, b) trend magnitudes and c) Mann-Kendall trend test. The data from the respectable meteorological station in Podgorica for the period from 1947 to 2018 were used in order to estimate the trend. The obtained results indicate a statistically significant positive trend for all analyzed time series. Analyzing the trend test hypotheses, it was concluded that in all three cases the Ha hypothesis prevails. Average annual air temperature in Podgorica increased by 1.4°C, average maximum air temperature increased by 2.5°C and average minimum air temperature increased by 0.6°C. In accordance with the trends analyzed, the increase in air temperature is dominant in the capital of the Republic of Montenegro.